Teachers’ Anxiety And Self-Efficacy: The Effect On Their English Skills Mastery - Laila Rochmawati; Fatmawati; Meita Maharani Sukma (Politeknik Penerbangan Indonesia Curug, 2023)
Teachers’ anxiety and self-efficacy in four English skills take an important role in succeeding the classroom learning activities. Thus, this study aimed to examine the effect of teachers’ anxiety and self-efficacy on their English skills mastery. The teachers’ English skills mastery was based on their TOEIC Scores. There were 65 teachers at one of the state polytechnics who participated voluntarily in the study. Data were obtained using Foreign Language Anxiety Scale (FLAS) and Foreign Language Self-Efficacy Scale (FLSS). Lecturers’ TOEIC scores were categorized into six levels namely novice, elementary, intermediate, basic working proficiency, advanced working proficiency, and general professional proficiency. The obtained data were analyzed using the descriptive-quantitative technique. The results showed that there was no notable effect of teachers’ anxiety in English on their English skills mastery. Another finding revealed a significant effect of teachers’ self-efficacy in mastering English on their English skills mastery. These results are expected to be a reliable source of rationales that initiating a development program of teachers’ self-efficacy in mastering English could enhance their English skills mastery.